New Approach to Aluminium-Polymer Alloys - Mohd Ichwan, Nasution; Mohd Nasir, Zainal Arif, Prof.; Che Mohd Ruzaidi, Ghazali, Assoc. Prof.; Shamsul Baharin, Jamaludin, Assoc. Prof. Dr.; Faizul, Che Pa; Murizam, Darus; Che Idrus, Omar; Lee Liu Mei (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.